A lower limb BOLD-MRI tissue perfusion protocol correlate to clinical disease stage, objective functional limitations, and health-related quality of life in patients with peripheral arterial occlusive disease - Joakim Nordanstig; Kristina Törngren; Jonathan Arvidsson; Stefanie Eriksson; Mårten Falkenberg; Åse Johnsson; Kerstin Lagerstrand (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2022)
While peripheral artery occlusive disease (PAOD) by large is a clinical diagnosis, further characterization of the ischemic state, procedural planning, and longitudinal follow-up after revascularisation are mainly based on imaging that delineates the arterial vasculature. Although several potential techniques have been suggested [1], there is still no clearly established imaging technique that directly quantifies the crucial PAOD pathophysiological process-tissue perfusion in the lower limb.